Risk Factors and Mechanisms Underlying Cross-Shift Decline in Kidney Function in Guatemalan Sugarcane Workers. Issue 3 (March 2019) - Sorensen, Cecilia J.; Butler-Dawson, Jaime; Dally, Miranda; Krisher, Lyndsay; Griffin, Benjamin R.; Johnson, Richard J.; Lemery, Jay; Asensio, Claudia; Tenney, Liliana; Newman, Lee S.
Abstract : Objective: Identify early biomarkers and mechanisms of acute kidney injury in workers at risk of developing chronic kidney disease of unknown origin (CKDu). Methods: We assessed cross-shift changes in kidney function and biomarkers of injury in 105 healthy sugarcane workers. We obtained pre-harvest clinical data as well as daily environmental, clinical, and productivity data for each worker. Results: The average percent decline in cross-shift estimated glomerular filtration rate (eGFR) was 21.8% (standard deviation [SD] 13.6%). Increasing wet bulb globe temperature (WBGT), high uric acid, decreased urine pH, urinary leukocyte esterase, and serum hyperosmolality were risk factors for decline in kidney function. Conclusions: Sugarcane workers with normal kidney function experience recurrent subclinical kidney injury, associated with elevations in biomarkers of injury that suggest exposure to high temperatures and extreme physical demands. Abstract : Supplemental Digital Content is available in the text